Where is the greatest potential for resource recovery in wastewater treatment plants?. (15th July 2022) - Renfrew, D.; Vasilaki, V.; McLeod, A.; Lake, A.; Danishvar, S.; Katsou, E.
Highlights: Structured approach developed to select regional resource recovery strategies. Multi-criteria analysis considering cost, carbon, 6 capitals, market and recovery. Market potential >25% for heat, phosphorus, hydrogen, VFAs, hydrogen and CO2 . Priority resources for UK model are heat, ammonia, EPS, struvite and biosolids. Selected technologies increased nitrogen and phosphorus recovery by 68% and 71%. Abstract: The restorative and regenerative ability of the circular economy has led to the rapid growth of this concept over the past decade, as it facilitates the broadly adopted principles of sustainable development and beyond, through restorative and regenerative actions. The water sector is poised to benefit from this transition, due to its intrinsic circularity and the resources it handles, predominantly found in wastewater, that are valuable and critical. Currently, the vast range of resource recovery technologies coupled with few industrial examples hinder strategic decision making. Resource recovery on a regional scale improves market share and mitigates investment risk, therefore, a structured approach has been developed for the selection of priority technologies to act as a guide for strategic planning. A representative UK wastewater model acts as the baseline, with multi-criteria analysis used to select resources and create an enhanced resource recovery scenario. It was found that implementing the recovery of 5 'priority resources' (and technology pathways) increased nitrogen and phosphorus recovery by 68% and 71%, respectively. Lastly, the need for a cross-cutting approach for the holistic assessment of circular solutions is discussed. Graphical abstract: Image, graphical abstract